PENGARUH MODEL GUIDED DISCOVERY LEARNING TERHADAP HIGH ORDER THINKING SKILLS SISWA KELAS XI - Mufida Nofiana (Universitas Majalengka, 2020)
High Order Thinking Skills (HOTS) are part of the 2013 curriculum provisions in Indonesian. The Guided Discovery Learning (GDL) is one of the learning models that suits in the 2013 curriculum. This research aims to determine the effect of the GDL model on students' HOTS on animal tissue material in class XI MIPA of SMA Negeri 1 Baturraden. The research subjects were students of class XI MIPA 1 as a control class and class XI MIPA 2 as an experimental class. Sampling was done by cluster random sampling technique. The research design uses a post-test only control group design. The time of the research was conducted in August-September 2019. Stages of the research includes: preparation, implementation and evaluation. Data analysis techniques using the T test, F test, and Eta test. The Result of this research are: there are find difference in average value of HOTS students between the experimental class and the control class (sig = 0.01). The application of the Guided Discovery Learning model affects HOTS students (sig = 0.01) with low strength (interaction coefficient = 0.392). Although this power is low, there is certainty about the difference in the average value of HOTS students between the experimental class and the control class caused by differences in the learning model used.